Popular Cultural Resistance of Makassar Students - Bahrul Amsal; Rukiana Novianti Putri; Jusnawati Jusnawati (Edumaspul: Jurnal Pendidikan, 2023)
Popular culture is often interpreted as the practice of pacifism over the instant and commercial superiority of mass culture. Students, as community members, cannot be separated from social reality, which intersects with popular culture on a daily basis. Hegemonic popular culture can become an arena for contesting students' reinterpretation practices to express their resistance to the values that are behind the presence of a cultural trend. The purpose of this study is to reveal first, students' popular cultural practices in relation to changes in orientation as a scientifically oriented, objective, and critical learning agent, and second, how students make resistance efforts from within popular culture to re-create meaning practices in order to avoid domination. cultural hegemony in capitalism. This research uses a descriptive-qualitative approach. Data analysis was carried out through three stages: data reduction, data presentation, and drawing conclusions. The results of the study found two main things. First, popular culture is a social construction of mass media, which is an important part of the birth of mass culture. Second, popular culture is an arena for contestation of the practice of redefining so that it can change the values of cultural capitalism into values of resistance.